The quarantine papers - Kalpish Ratna (HarperCollins Publishers India, a joint venture with the India Today Group, 2010)
Ishrat Syed and Kalpana Swaminathan are surgeons. The anonym Kalpish Ratna is an almost anagram of their first names. This is their first Ratan/Ramratan Oak novel.--P.[407]